Human epidermal growth-factor receptor 2 overexpression in gastric carcinoma in Thai patients - Pattana Sornmayura (2018)
Objective: To determine human epidermal growth-factor receptor 2 (HER2) protein-overexpression frequency and the concordance rate between immunohistochemistry and fluorescence in situ hybridization techniques in gastric carcinoma. Material and Method: A retrospective analysis of gastric adenocarcinomas obtained from 224 adult patients between January 2000 and December 2008 were performed. The paraffin-embedded tissues were sliced into 4-μm-thick sections and analyzed for HER2 protein expression levels by immunohistochemistry (IHC) using an automated slide-staining IHC system. Breast carcinoma tissues were included in every staining batch as positive control. In order to detect and quantify amplification of the HER2, the authors performed fluorescence in situ hybridization (FISH) using PathVysion ® HER2 DNA Probe Kit. The IHC results were independently recorded by two pathologists using the standard HER2 scoring system for gastric carcinoma. FISH results were interpreted using standard guideline as employed in breast carcinoma. The two-tailed-Fisher's exact test was used to assess the concordance between IHC and FISH results. Results: HER2 protein overexpression level was identified in 9% (20 in 224 cases) of the gastric tumors; 80% of which were well or moderately differentiated and of the intestinal or mixed type. However, HER2-overexpressing tumors comprised only 16% of the intestinal/mixed-type or well/moderately differentiated tumors. There was no signal obtained from 29 specimens from FISH studies. Thus, the overall results of IHC and FISH methods were concordant in 88% (171 out of 195, p < 0.001). Conclusion: There is a significant concordance rate between IHC and FISH in gastric carcinoma. The present study is the first HER2 study of such carcinoma in Thai patients.